Environmental and Spiritual Leadership: Tracing the Synergies from an Organizational Perspective - Crossman, Joanna (Journal of business ethics, 2011)
This article presents some synergies that appear to exist in the conceptualization of environmental and spiritual leadership. After some discussion of the contexts in which environmental and spiritual leadership have arisen, the author identifies some commonalities in the underpinning values and associated discourse adopted in the literature to describe these two concepts. Common values include notions of the common and social good, stewardship, sustainability, servanthood, calling, meaning, and connectedness. The article also draws attention to the way that historical and cultural factors have contributed to some overlapping in the conceptual development of spirit and environment. Finally, avenues for demonstrating and embedding both spiritual and environmental leadership into organizations are explored.